1993
DOI: 10.3354/meps092015
|View full text |Cite
|
Sign up to set email alerts
|

A model of survival and growth of striped Pass larvae Morone saxatilis in the Potomac River, 1987

Abstract: ABSTRACT. A StellaTM lnodel based on laboratory-derived growth data was developed to simulate abundances, cohort survival and growth rates of striped bass eggs and larvae. The goal was to compare the simulations to 1987 field survey results from the Potomac River (Cheasapeake Bay, USA). Key factors in the model were striped bass egg production, water temperature, surface light and penetration, turbidity and zooplankton concentration. Growth and survival were simulated from the predicted effects of turbidity. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Previous work on potential retention mechanisms indicated that larval striped bass (Morone saxatilis) remained at depth in the LSZ regardless of tidal direction or time of day, and that longfin smelt (Spirinchus thaleichthys) were abundant in surface waters as yolk-sac and young postlarvae and occurred progressively deeper as they grew larger (Wang 1986;Fujimura 1991). These findings are consistent with those from the Chesapeake Bay estuary, where larval striped bass have been observed to occur regularly in the lower two-thirds of the water column (Kernehan et al 1981;Chesney 1993). North and Houde (2001) recently showed that younger postlarvae were positioned near the surface while older postlarvae were positioned near the bottom.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Previous work on potential retention mechanisms indicated that larval striped bass (Morone saxatilis) remained at depth in the LSZ regardless of tidal direction or time of day, and that longfin smelt (Spirinchus thaleichthys) were abundant in surface waters as yolk-sac and young postlarvae and occurred progressively deeper as they grew larger (Wang 1986;Fujimura 1991). These findings are consistent with those from the Chesapeake Bay estuary, where larval striped bass have been observed to occur regularly in the lower two-thirds of the water column (Kernehan et al 1981;Chesney 1993). North and Houde (2001) recently showed that younger postlarvae were positioned near the surface while older postlarvae were positioned near the bottom.…”
supporting
confidence: 88%
“…Although we are unaware of information on the vertical distributions of yellowfin goby and shimofuri goby in their native estuaries, striped bass larvae have not been previously reported to undertake vertical migrations. In the Hudson river estuary, investigators have hypothesized that vertical movements may occur on diel basis (Smith 1988), and in the Chesapeake postlarval striped bass appear to occur regularly in the lower two-thirds of the water column (Kernehan et al 1981;Chesney 1993;E. Houde pers.…”
Section: Discussionmentioning
confidence: 99%
“…Growth during the larval stage plays a critical role in recruitment, because slow growth increases the duration of a developmental stage and thus mortality (Shepherd and Gushing 1980;Houde 1987;Anderson 1988). In simulation studies, Chesney (1993) demonstrated that cohort-specific growth…”
Section: Discussionmentioning
confidence: 99%
“…Rose & Cowan (1993) and Letcher et al (1996) used a length-dependent expression from bluegill sunfish Lepomis macrochirus derived by Breck & Gitter (1983). Chesney (1993) developed a model for bass larvae with light, turbidity and prey density represented directly from empirical functions. These authors (and others) made feeding depend on a lower light threshold, below which feeding did not occur, so that feeding was restricted to a prescribed fraction of the day.…”
Section: The Modelmentioning
confidence: 99%